Metastatic Testicular Germ Cell Tumor or a Chemoresponsive Liver Hemangioma? - Ferreira, J. (2012)
Testicular germ cell tumors are the most common solid organ malignancy in young adult men. The presence of non-pulmonary visceral metastasis is an independent factor that places such patients into the higher risk group. Hepatic hemangiomas are the most common tumors of the liver and are entirely benign. Overlap between these entities may occur, particularly when metastases are hypervascular. We describe a case of a 27-year-old man with a testicular germ cell tumor and a nodule in the right hepatic lobe suggestive of hemangioma. After three cycles of chemotherapy, a size reduction in the hepatic nodule was confirmed, and this lesion was removed. Pathology revealed a fibrosing hemangioma. In this case report, the authors discuss the possible mechanisms for the hemangioma chemotherapy response.